Induction of osteoclastogenesis and bone loss by human autoantibodies against citrullinated vimentin - Georgess, Dan (2012)
Autoimmunity is complicated by bone loss. In human rheumatoid arthritis (RA), the most severe inflammatory joint disease, autoantibodies against citrullinated proteins are among the strongest risk factors for bone destruction. We therefore hypothesized that these autoantibodies directly influence bone metabolism. Here, we found a strong and specific association between autoantibodies against citrullinated proteins and serum markers for osteoclast-mediated bone resorption in RA patients. Moreover, human osteoclasts expressed enzymes eliciting protein citrullination, and specific N-terminal citrullination of vimentin was induced during osteoclast differentiation. Affinity-purified human autoantibodies against mutated citrullinated vimentin (MCV) not only bound to osteoclast surfaces, but also led to robust induction of osteoclastogenesis and bone-resorptive activity. Adoptive transfer of purified human MCV autoantibodies into mice induced osteopenia and increased osteoclastogenesis. This effect was based on the inducible release of TNF-α from osteoclast precursors and the subsequent increase of osteoclast precursor cell numbers with enhanced expression of activation and growth factor receptors. Our data thus suggest that autoantibody formation in response to citrullinated vimentin directly induces bone loss, providing a link between the adaptive immune system and bone.